Macroeconomics - Mankiw, N. Gregory (New York, NY : Worth Publishers, 2003)
In this book the author tries to offer a balance between short-run and long-run issues in macroeconomics. The book also integrates the insights of Keynesian and classical theories. Many of the contributions of the classical economist before Keynes and the new classical economists of the past two decades are integrated. It also gives a substanctial coverage to the IS-LM model of aggregate demand, the short-run tradeoff between inflation and unemployment, and modern theories of wages and price rigidity. This book contains numerous case studies that use macroeconomic theory to shed light on real-world data or events. The case studies teach the reader how to apply economic principles to issues from fourteenth century Europe, the island of Yap, the land of Oz, and today's newspaper.
Includes bibliographical references and index.
rpm 2810/13
Loans
Keywords: Macroeconomics